2023
DOI: 10.1007/s00216-023-04571-4
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatically mediated fluorescent copper nanocluster generation for tyramine determination

Abstract: This work details the enzymatic generation of fluorescence nanomaterials and the use of this optical signal as the analytical parameter for the quantification of the substrate. More specifically, fluorescent copper nanoclusters have been obtained during the enzymatic reaction of tyramine oxidase and tyramine in the presence of Cu(II); the fluorescence intensity being proportional to the concentration of tyramine. The nanoclusters obtained show fluorescence at 445 nm by being excited at 320 nm and have been ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previous works of the research group have demonstrated that oxidase-type enzymes are able to reduce the metallic ion to stable nanomaterials which optical properties (absorption, uorescence] can be related to the concentration of the corresponding analyte [11,12]. In this sense, the determination of tyramine with Tyramine oxidase (with copper as cofactor) has been carried out through the absorption band of the in-situ AuPtNPs [13] or the uorescence of CuNCs [14]. Flavoenzymes such as Glucose oxidase or Putrescine oxidase have also been studied [15].…”
Section: -Introductionmentioning
confidence: 99%
“…Previous works of the research group have demonstrated that oxidase-type enzymes are able to reduce the metallic ion to stable nanomaterials which optical properties (absorption, uorescence] can be related to the concentration of the corresponding analyte [11,12]. In this sense, the determination of tyramine with Tyramine oxidase (with copper as cofactor) has been carried out through the absorption band of the in-situ AuPtNPs [13] or the uorescence of CuNCs [14]. Flavoenzymes such as Glucose oxidase or Putrescine oxidase have also been studied [15].…”
Section: -Introductionmentioning
confidence: 99%
“…Our group has developed colorimetric methods for the determination of Tym and other substrates [20] based on the generation of gold nanoparticles [21,22] (or other nanomaterials [23]) and the measurement of its optical properties, by coupling a previous enzymatic oxidation of tyramine with O 2 catalyzed by tyramine oxidase (TAO) [24]. Here, an alternative methodology for the development of rapid methods based on the in-situ and direct generation (without coupling any other type of reaction) of gold nanoclusters is presented.…”
Section: Introductionmentioning
confidence: 99%